Evaluation of the nipple-areola complex after reduction mammoplasty with dermal release versus resected volume of the breast tissue - Jairo Zacchê De-Sá; Kelson Kawamura; Rafael Henrique Coutinho Barreto; Anderson da Silva Ramos; Amanda Torres Campos; Antônio Carlos Corte Real Braga (Revista Brasileira de Cirurgia Plástica)
Introduction: The nipple-areola complex (NAC) plays an important role both in breastfeeding and sexual lives of the patients. Because of this, we must mention possible complications of reduction mammoplasty, such change or even loss of sensitivity of the NAC. Method: This was a prospective, randomized, controlled, double-blind study to evaluate the relationship between the sensitivity of the NAC after reduction mammoplasty with dermal release and the resected volume of breast tissue. This study was conducted between August 2013 and August 2015 at the Hospital das Clínicas of the Federal University of Pernambuco (HC-UFPE), in Recife City, Brazil. Results: The study involved 39 patients. The mean age and body mass index (BMI) of the patients were 31.7 years and 25.5 kg/m2, respectively. None of the patients was a smoker. The complication rate was 41%, including 7 cases of non-aesthetic scars, 6 cases of hematoma (bruises), and 4 cases of dehiscence. No patient had pain or NAC necrosis, and all the patients expressed being satisfied with the final surgical result. No statistically significant differences were found between the patients of the experimental and control groups, both in the group with resection of up to 300 g and those with resection >300 g. Conclusions: The maneuver of dermic release did not result in any differences in the sensitivity of the NAC, regardless of the quantity of resected breast tissue.